Natural Hazard Vulnerability and Risk Assessment: The Case of the China-Pakistan Economic Corridor - Abid Ejaz Kahloon; Shaheen Akhtar (NUST Journal of Social Sciences and Humanities, 2023)
The coverage area of the China-Pakistan Economic Corridor (CPEC) in Pakistan, including its critical functional zones within which major projects are located, is prone to different types of natural hazards and disasters. Since 2015, efforts have been made to operationalize CPEC without institutionalizing and establishing a comprehensive natural hazard risk assessment mechanism within the China-Pakistan collaborative framework. It goes against the grain of robust, resilient, and sustainable long-term development of CPEC. This study critically argues for the need to set up a multi-hazard risk assessment and disaster response mechanism as part of the institutional framework of CPEC, responsible for identifying, preparing, and planning against primary, secondary, and tertiary risks in accordance with the varied hazard vulnerability prevalence in varying geospatial and functional zones within the coverage area of CPEC. Overall, the study identifies and discusses the risk-prone nature of the current development of CPEC and proposes a real-time, technologically enabled, natural hazard risk assessment of CPEC projects spread over varying geospatial and functional zones in an institutional framework characterized by the uninterrupted collaboration and concentration of experts and resources from China and Pakistan.